Poultry Farmers Perceived Constraints and Unwholesome Practices among Feed Mill Industries in Ibadan Metropolis - o, Eniola. (International Journal of Environment, Agriculture and Biotechnology, 2019)
In order to investigate poultry farmers perceived constraints and unwholesome practices among commercial feed mill industries in Ibadan metropolis. Purposive sampling procedure was used for this study and a total of ninety six questionnaires were administered to the farmers out of the one hundred and sixty registered poultry farmers with Oyo State Agricultural Development Project (OSADEP) in Ibadan metropolis. The socio-economic characteristics of the respondents such as age, marital status, educational level, gender, years of experience, religion were assessed using descriptive statistics, frequency and percentage, while farmer’s perceptions on unwholesome practices and types of feed ingredients used and sources were measured using chi-square analytical tool. Other questions like benefits derived and constraints facing self milling in poultry industries were measured using Pearson product method of correlation (PPMC). From the findings it was revealed that majority of the farmers were facing one challenges or the otheras a result of some sharp practices by the so called feed mill industries in Ibadan ranging from poor quality of feeds sold to farmers, short changing the customers in terms of measurement, scarcity of feed ingredients, seasonal instability in agricultural grains among others. Also, (61.5%) of the farmers agreed that already spoilt feed ingredients can easily be detected since they are not usually bought in large quantities which is one the benefits farmers derived from self milling.